Dynamics of caste and early childbearing in India: a perspective of three decades - Manas Ranjan Pradhan; Sourav Mondal; Daisy Saikia; Prasanna Kumar Mudi (BMC, 2024)
Abstract Background Early childbearing disrupts girls' otherwise healthy growth into adulthood and adversely affects their education, livelihood, and health. Individual, sociocultural, economic, environmental, and health service-related factors contribute to childbearing among young females. In India, caste affects health outcomes despite several affirmative policies aimed at improving the health and welfare of the backward castes/tribes. However, there is a dearth of empirical evidence about the impact of caste on early childbearing, more specifically, regarding the trajectory of inter-caste disparities in early childbearing. Method This study used data from all five rounds of the National Family Health Survey (NFHS) in India to assess the association between caste and early childbearing over the last three decades. All women aged 20-24 [NFHS-1 (n = 17,218), NFHS-2 (n = 15,973), NFHS-3 (n = 22,807), NFHS-4 (n = 122,955) and NFHS-5 (n = 118,700)] were considered to create a pooled data set (n = 297,653) for analysis. Bivariate analysis and binary logistic regression were conducted using Stata (v17). ArcMap (v10.8) presented the caste-wise prevalence of early childbearing among the states and Union Territories (UTs). Results Many women continue to have early childbearing despite a considerable reduction over the last three decades from 47% in 1992-93 to 15% in 2019-21. Compared to NFHS-1, the odds of early childbearing increased by 15% in NFHS-2 and, after that, declined by 42% in NFHS-3 and 64% in NFHS-4 and NFHS-5. The inter-caste disparity in early childbearing persists, albeit with a narrowing gap, with the Scheduled castes (SC) remaining the most vulnerable group. Adjusting the effects of socio-demographic and economic characteristics, SC women had significantly higher odds of early childbearing (OR = 1.07, CI = 1.04-1.11) than those from the General caste. Conclusion To decrease early childbirth, a focus on adolescent marriage prevention and increasing contraceptive use among young SC women is necessary. Strengthening ongoing programs and policies targeting educational and economic empowerment of the socially weaker castes/tribes will help in reducing early childbearing. Efforts to prevent early childbearing will accelerate the achievement of the Sustainable Development Goals (SDGs)-especially those related to health, poverty, nutrition, education, and general wellbeing, in addition to protecting women's reproductive rights.